Late relapse of diabetes after bariatric surgery should not be considered as a failure - Aminian, Ali; Nor Hanipah, Zubaidah; Sharma, Gautam; Chao, Tu; Brethauer, Stacy A.; Schauer, Philip R.; Mahawar, Kamal (Elsevier, 2018)
Background: Although the impressive metabolic effects of bariatric surgery in patients with Type 2 Diabetes (T2DM) are known, bariatric surgery is criticized for late relapse of diabetes.